Apolipoprotein E ε4 Allele-Based Differences in Brain Volumes Are Largely Uniform Across Late Middle Aged and Older Hispanic/Latino- and Non-Hispanic/Latino Whites Without Dementia - Stickel, Ariana M.; McKinnon, Andrew C.; Matijevic, Stephanie; Grilli, Matthew D.; Ruiz, John; Ryan, Lee (Frontiers in Aging Neuroscience, 2021)
Hispanics/Latinos are at an equal or a greater risk for Alzheimer's disease (AD), yet risk factors remain more poorly characterized as compared to non-Hispanic/Latino Whites. Among non-Hispanic/Latino White cohorts, the apolipoprotein E (APOE) ε4 allele is one of the strongest risk factors for AD with subtle declines in episodic memory and brain volumes detectable in the preclinical stages. We examined whether the APOE ε4 status had a differential impact on cognition and brain volumes among cognitively healthy and mild cognitively impaired Hispanics/Latinos (n = 86; ε4 n = 23) compared to a well-matched group of non-Hispanic/Latino Whites (n = 92; ε4 n = 29). Neither the APOE ε4 status nor the interaction between the ε4 status and ethnicity was associated with cognitive performance. The APOE ε4 status was associated with white matter and not with gray matter volumes. APOE ε4 carriers had a significantly smaller total brain white matter volumes, as well as smaller right middle temporal and left superior temporal volumes. The Hispanics/Latinos had significantly smaller left middle frontal gray matter volumes, yet marginally larger overall white matter volumes, than the non-Hispanic/Latino Whites. Exploratory analysis within the Hispanic/Latino sample found that those people whose primary language was Spanish had larger total brain white matter volumes compared primarily to the English speakers. Importantly, primary language differences only held for Hispanic/Latino ε4 carriers and did not differentiate Hispanic/Latino non-carriers, underscoring the need for further investigation into the impacts of language and acculturation on cognitive aging among the fastest growing ethnic minority group in the United States.